Dampak Pandemi Covid-19 Terhadap Pergeseran Lapangan Usaha PDRB Kabupaten dan Kota di Provinsi Sumatera Selatan - Susyanto Tunut; Ratih Eka Sakti (IPM2KPE, 2023)
This study aims to analyze the impact of the Covid-19 pandemic on shifts in business fields in Regency and City GRDP in South Sumatra Province. The research method used is descriptive quantitative. The results of the study are (1) the average GRDP in the Regency Region after the pandemic increased from 14,444.63 to 16,831.04. This shows that there has been a recovery in the contribution of the Business Field to GRDP. The Business Fields which contributed quite a lot (2.7 percent) but have not yet recovered are Real Estate; (2) The average GRDP in the City Region after the pandemic fell from 27,459.3 to 19,272.2. This shows that there has been no recovery of GRDP; (3) The results of the quadrant analysis show that the shift in Business Fields that occurs is caused by a decreased contribution to GRDP, slowing growth in Business Fields, and a combination of both. In conclusion, there is a shift in Business Field which has a significant contribution to changes in GRDP in the City area. Keywords: GRDP Shift, Impact of the Covid-19 Pandemic